1993
DOI: 10.1007/bf02783169
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity and teratogenicity of uranium in mice following subcutaneous administration of uranyl acetate

Abstract: The effects of multiple maternal subcutaneous injections of uranyl acetate dihydrate (0.5, 1, and 2 mg/kg/d) from d 6 to d 15 of gestation were evaluated in Swiss mice. External, internal soft-tissue and skeletal examinations of fetuses were performed on gestation d 18. Maternal toxicity occurred in all uranium-treated groups as evidenced primarily by deaths as well as significant decreases in weight gain and in body weight at termination. Although it was not dose-related, embryotoxicity also occurred in all u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Domingo et al (1989) reported that perinatal and postnatal exposure of Swiss mice to uranium-as uranyl acetate dihydrate-at daily dosages of 0, 0.05, 0.5, 5, and 50 mg/kg from d 13 of pregnancy until weaning of the litters on postnatal d 21 showed significant decreases in the mean litter size on postnatal d 21, and in the viability and lactation indices were observed at the 50-mg/kg/d dose level. Bosque et al (1993) reported that fetal body weight was significantly decreased in mice at 1 and 2 mg/kg/d exposure to uranium. They reported the number of total internal and total skeletal defects showed dose-dependent increases at 0.5, 1, and 2 mg/kg/d.…”
Section: E S Craft Et Almentioning
confidence: 99%
“…Domingo et al (1989) reported that perinatal and postnatal exposure of Swiss mice to uranium-as uranyl acetate dihydrate-at daily dosages of 0, 0.05, 0.5, 5, and 50 mg/kg from d 13 of pregnancy until weaning of the litters on postnatal d 21 showed significant decreases in the mean litter size on postnatal d 21, and in the viability and lactation indices were observed at the 50-mg/kg/d dose level. Bosque et al (1993) reported that fetal body weight was significantly decreased in mice at 1 and 2 mg/kg/d exposure to uranium. They reported the number of total internal and total skeletal defects showed dose-dependent increases at 0.5, 1, and 2 mg/kg/d.…”
Section: E S Craft Et Almentioning
confidence: 99%
“…For example, administration (s.c.) of uranium in the form of uranyl acetate dihydrate (0.5-2.0 mg/kg/d) to gravid (pregnant) mice from gestational days (GD) 6-15 leads to significant decreases in both maternal weight gain and fetal body weights at GD 18 3 . Soft tissue and skeletal examination of the fetuses also revealed a significant increase in the occurrence of renal hypoplasia in all uranium-treated groups.…”
Section: Uranium-induced Fetal and Developmental Toxicitymentioning
confidence: 99%
“…A dose-dependent association between uranium exposure and altered development of the skeletal system, including unossified sternebrae and reduced ossification in caudal, parietal, occipital, carpal, vertebral, and metatarsal bones, was reported in various studies where Swiss albino mice exposed during gestation (Bosque et al, 1992(Bosque et al, , 1993aDomingo et al, 1989). The uraniuminduced alterations in fetal bone development were among the most sensitive developmental effects observed in the developing mouse fetus (Bosque et al, 1993b;Domingo et al, 1989).…”
Section: Uranium-induced Bone Toxicitymentioning
confidence: 93%